Analisis Penjatuhan Hak Hadhanah pada Perempuan dalam Tinjauan Maqashid As-Syari’ah - Muhammad Zainuddin Sunarto; Diah Uswatun Hasanah (CV Rewang Rencang, 2025)
Hadhanah in Islamic law, which are usually given to mothers, from the point of view of Maqashid as-Syari'ah according to Imam Al-Syatibi. Emphasizes that custody rights must be based on the child's benefit in accordance with the five main objectives of Maqashid as-Syari'ah. UUD No. 23 of 2002 also emphasizes the best interests of children. As a result, the proper hadhanah needs to be applied flexibly and comprehensively, balancing the duties of social support, motherhood, and fatherhood. flexible legal regulations are required to preserve children's wellbeing and strike a balance between parents' rights and responsibilities.